Advances in cGAS-STING Signaling Pathway and Diseases - Yang, Yuting; Huang, Yiming; Zeng, Zhenguo (Frontiers in Cell and Developmental Biology, 2022)
Pathogens can produce conserved pathogen associated molecular patterns (PAMPs) after invading to the body, which can be specifically recognized by host pattern recognition receptors (PRRs). In recent years, it was found that cytoplasmic DNA receptors recognize exogenous DNA inducing activation process of interferon 1 (IFN1), which are rapid advances in various research areas. Cyclic GMP–AMP synthase(cGAS) stimulator of interferon gene (STING) signaling pathway is a critical natural immune pathway in cells. Early studies revealed that it plays a crucial regulatory role in pathogen infection and tumor, and it is associated with various human autoimmune diseases. Recently studies have found that activation of cGAS-STING signaling pathway is related to different organ injuries. The present review elaborates on the regulation of cGAS-STING signaling pathway and its role in various diseases, aiming to provide a theoretical basis for immunotherapy targeting this pathway.